An intersectional exploration of the motherload among black mothers in professional occupations in South Africa - Somo, Moletlo (Organisational Psychology, 2026)
Recent work-family research has begun recognising the most invisible aspects of unpaid care work to be the physical, cognitive and emotional care load placed on women. The concept of the motherload, which describes the “highly gendered, often invisible, and undervalued work that those who perform mothering undertake hindering their economic security, safety and wellbeing”, was explored through semi-structured in-depth interviews with 11 Black mothers in professional occupations in South Africa. The data were analysed through an intersectional analytical lens to understand how motherhood, race and professional occupation shapes the experiences of the motherload. The study's findings revealed the ways in which the Black working mothers experienced the motherload as they navigated the cultural expectations in the household and community, as well as their professional workplace identity. Three key themes were analysed which underscored the cultural care load placed on Black women and how that shapes the motherload through (1) Jostling between tradition and modernity: Black women navigating the motherload, (2) Black tax and caring beyond the household, and (3) Cultural dissonance and carrying the motherload. Recommendations were presented for improving the retention and attraction of Black working mothers through recognising the motherload within the workplace.